Coping with water scarcity in the irrigated lowlands of the lower Amudarya basin, Central Asia - Bekchanov, Maksud; Lamers, John P.A.; Martius, C. (2014)
Improving irrigation efficiency is of utmost importance in the irrigated lands of Central Asia, such as the Khorezm region of Uzbekistan, since water misuse and subsequent soil salinization threaten environment, economy, and livelihoods. To this end, several field-level ‘water-wise’ innovations were selected, which are classified into four groups that address crop pattern change, soil moisture maintenance, uniform water distribution, and furrow irrigation improvement. The potential of these innovations to raise irrigation water use efficiency from its current low level was analyzed from a socio-economic and technical point of view with a focus on short-term measures to cope with sudden water shortages. The overall water use reduction potential of these options was estimated considering their adoption feasibility within the time horizon of one year. To prioritize the examined innovations according to their contribution to overall water use reduction and water profitability, ‘marginal water profitability curves’ were developed. This integrated approach could serve as a simple but effective policy tool. The findings indicate that the option of replacing rice by maize contributes to more than 50 % of the total possible water use reduction. However, while all the other options increase the total revenue, reduced revenues will be unavoidable when paddy rice is replaced by maize. Manuring provides the highest additional profit per volume of reduced water use, but contributes less than 10 % of the total water use reduction potential. With water-wise options as an immediate and short-term measure to cope with sudden water shortages, the theoretical total estimated water reduction at the field level amounts to 183 – 376,000,000 m3 or 9.0 – 18.5 % of the current total irrigation water requirement in the region. For coping with sudden shortages characterized by a water availability of only 60 % of the normal water supply, long-term planning and management of irrigation activities focusing on a wider adoption of advanced irrigation technologies are necessary.